Biomimetic synthesis of the natural product salviadione and its hybrids: discovery of tissue-specific anti-inflammatory agents for acute lung injury. Issue 17 (28th March 2019) - Ding, Chunyong; Chen, Hongjin; Liang, Bin; Jiao, Mingkun; Liang, Guang; Zhang, Ao
Abstract : Biomimetic synthesis of the natural product salviadione and its hybrids was achieved leading to tissue-specific anti-inflammatory agents for acute lung injury. Abstract : Acute lung injury (ALI) is an inflammatory disease with no effective pharmacological treatment. The therapeutic potential of the anti-inflammatory natural product tanshinone IIA (2 ) for ALI is seriously impaired by its poor pharmacokinetic (PK) properties. Inspired by the unique benzo[ def ]carbazole-3, 5-dione (BCD) core of the natural product salviadione (5 ), a series of furan-fused BCD hybrids of5 with2 was rationally designed with the aim to improve both PK properties and the anti-inflammatory activity. A biomimetic synthetic approach featuring one-pot tandem N-heterocyclization was first developed for convenient assembly of salviadione (56% overall yield over 2 steps) and the designed hybrids (35–85% yields in one step). Compared to2, most of the resulting compounds exhibited a markedly enhanced inhibitory effect against LPS-induced release of pro-inflammatory cytokines in macrophages. Particularly, compound15a not only possessed the most potent activity in vitro, but also exhibited significantly improved metabolic stability (4- to 7-fold enhancement), pharmacokinetic properties ( T 1/2 = 4.05 h; F = 30.2%), and preferable lung tissue distribution (11- to 300-fold selectivity). An in vivo study in mice showed that pretreatment with15a at 5 mg kg −1 distinctly attenuated LPS-induced ALI via lung tissue-specific anti-inflammatory actions, indicating that the furan-fused BCD core presents a unique chemotype with promising therapeutic potential for ALI.